Functional Food - Monica Butnariu; Ioan Sarac (International Journal of Nutrition, 2019)
The notion that foods have health promotion effects beyond their nutritional value has been increasingly accepted in recent years, and the specific effects of nutrition prevention on disease have led to the discovery of functional foods. Functional foods are products that contain various biologically active compounds and which, consumed in a current diet, contribute to maintaining the optimal state of physical, mental and mental health of the population. Functional foods are consumed in the normal diet and contain biologically active compounds with potential to improve health or to reduce the risk of disease. The objectives of this review are to highlight the strengths of functional foods.
Keywords: functional food